Ocena funkcjonowania audytu wewnętrznego w jednostkach samorządu terytorialnego w świetle badań empirycznych - Filipiak, Beata; Dylewski, Marek (An Appraisal of Internal Audit in Local Government - Empirical Research, 2009)
The article presents empirical research within the range of internal audit in local government. This research was carried out thanks to a grant by the Polish Ministry of Science and Higher Education. The article - among others - describes indications concerning directions of evolution of internal audit in local government.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 39-49